Ginsenoside Rg1 and Acori Graminei Rhizoma Attenuates Neuron Cell Apoptosis by Promoting the Expression of miR-873-5p in Alzheimer’s Disease - Shi, Ran; Zhang, Sishuo; Cheng, Guangqing; Yang, Xiaoni; Zhao, Ningning; Chen, Chao (Neurochemical research, 2018)
Alzheimer’s disease (AD) severely threatens human health in their old age, however the potential etiology underlying it is still unclear. Both Ginsenoside Rg1 (GRg1) and Acori graminei Rhizoma (AGR) are the traditional Chinese herbal drug, while their potential role in AD remains need further identification. Both SAMP1 and SAMP8 mice were employed as the control and AD mice. Morris water maze method was used to detect the cognitive function of the mice, TUNEL assay was performed to determine cell apoptosis. Real-time PCR and western blot were carried out to measure gene expression. The relationship between miR-873-5p and HMOX1 was determined using luciferase reporter assay. Comparing with SAMP1, the cognitive function was impaired and cell apoptosis was increased in SAMP8 mice. GRg1 + AGR treatment significantly attenuated the symptom of AD. The expression of miR-873-5p was decreased, while HMOX1 was increased in SAMP8 mice. GRg1 + AGR treatment significantly promoted the expression of miR-873-5p, but decreased HMOX1. MiR-873-5p targets HMOX1 to regulate its expression. Aβ1–42 stimulation decreased the expression of miR-873-5p, but increased HMOX1 in PC12 cells. GRg1 + AGR treatment reversed the effect of Aβ1–42, while miR-873-5p inhibitor abolished the effect of GRg1 + AGR. In vivo experiments confirmed the protect role of GRg1 + AGR in AD. GRg1 + AGR suppressed neuron cell apoptosis by regulating the expression of miR-873-5p in AD.